Prevalence and sociodemographic factors associated with stunting and thinness in adolescent females: a cross sectional study from Pakistan - Samo, Ayaz Ali; Laghari, Zulfiqar Ali; Memon, Aslam; Baig, Nimra Masood; Memon, Salma Farukh; Shaikh, Shakeel Ahmed (Journal of the Pakistan Medical Association, 2021)
Objective: To explore the prevalence and socio-demographic factors associated with stunting and thinness in adolescent females. Method: The survey-based cross-sectional study was conducted in randomly selected schools of the Kotri Taulka of Jamshoro District in Sindh, Pakistan, from October to December 2019, and comprised healthy female adolescents aged 1019 years. Data about demographic and anthropometric factors was collected using a pre-tested questionnaire. Data was analysed using SPSS 23. Results: There were 393 subjects with mean age 14.93±2.18 years, mean weight 45.9±8.85kg, and mean height 151.6±6.25cm. The prevalence of stunting and thinness was 127(32.31%) and 42(10.68%) respectively. Stunting was more frequent in participants with father’s income ?15000 Pak rupees (p<0.05). Conclusion: The increased prevalence of stunting and thinness in adolescent females needs to be addressed by the policy-makers. Key Words: Stunting, Thinness, Adolescent, Females, Sindh, Pakistan. Continuous....